Speaking out on one’s own sexual victimization : How does social movement engagement affect sexual violence survivors in Iceland? - Sigurbirna Hafliðadóttir 1978- (2022)
While people worldwide are impacted by sexual violence daily, it wasn’t until 2017, with the start of the #MeToo movement, that massive numbers of survivors publicly shared their personal trauma. The purpose of this study is to investigate how being a part of such a movement affects people's well-being and ability to heal from personal trauma. A qualitative research approach utilizing in-depth semi-structured interviews was conducted. Five Icelanders who were involved in Iceland’s’ #MeToo movement were interviewed and the data gathered was categorized into themes. The findings indicated that the participants feel empowered and that the support they receive helps them heal, with some claiming that returning the shame to the perpetrators relieved them of a burden they had carried for years. Participants also disclose negative effects; among other how the debate could easily turn into nasty comments and some even experiencing harassment online. They also described burning out and needing to take a break. Further studies should among other aim at assessing if nonparticipating sexual violence survivors might experience healing effects from the #MeToo movement. Keywords: #MeToo, sexual violence, healing, empowerment, Social Movement Á hverju ári verður fólk um allan heim fyrir kynferðislegri misnotkun og áreitni. #MeToo hreyfingin kom fram árið 2017. # MeToo hreyfingin einbeitir sér að hvers kyns kynferðislegri áreitni og ofbeldi, með það að markmiði að afhjúpa vandamálið, með opinberum frásögnum einstaklinga af áföllum. Þessi rannsókn miðar að því að skoða hvaða áhrif það hefur á líðan fólks og heilunarferli þess af persónulegum áföllum samhliða því að vera þátttakandi í slíkri hreyfingu. Í rannsókninni var notast við eigindlega rannsóknarnálgun með ítarlegum hálf opnum viðtölum. Fimm einstaklingar á Íslandi sem komu að #MeToo hreyfingunni á Íslandi komu í viðtal og söfnuð gögn voru unnin í þemu. Niðurstöðurnar benda til þess að þátttakendur finni fyrir valdeflingu og að stuðningurinn sem þeir fengu hafi haft ...